2022
DOI: 10.1002/csc2.20675
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of environment and cultivar impact on lentil protein, starch, mineral nutrients, and yield

Abstract: Lentil (Lens culinaris Medik.) is an important source of protein, starch, and mineral nutrients in many parts of the world. However, the impact of environment and cultivar on the enrichment of these nutrients is not well understood. Four lentil cultivars (‘Avondale’, ‘CDC Richlea’, ‘CDC Maxim’, and ‘CDC Imvincible’) varying in color, seed size, and maturity were evaluated at five Montana locations with diverse climatic and soil conditions over 3 yr. Significant cultivar, location, and year effects were found f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
18
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 65 publications
6
18
1
Order By: Relevance
“…Seed mineral macronutrient contents (P, K) were also influenced by the environment (EV% > 92%) with the exception of seed K under organic farming where G × E effects explained 32.4% of the total variation ( Table 1 ). These results are partially in agreement with those of Chen et al [ 47 ] who found that beside environmental effects, cultivar selection is also very influential on lentil seed mineral nutrient concentrations (including P, K and secondary macronutrients, S, Ca, Mg) for lentils grown after wheat, barley, alfalfa or chemical fallow. On the other hand, our results comply to those by Vandemark et al [ 18 ] who found that for the majority of minerals in lentil seed the highest interaction effect was the location × year (i.e., Environment) effect in two locations in Washington (US).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Seed mineral macronutrient contents (P, K) were also influenced by the environment (EV% > 92%) with the exception of seed K under organic farming where G × E effects explained 32.4% of the total variation ( Table 1 ). These results are partially in agreement with those of Chen et al [ 47 ] who found that beside environmental effects, cultivar selection is also very influential on lentil seed mineral nutrient concentrations (including P, K and secondary macronutrients, S, Ca, Mg) for lentils grown after wheat, barley, alfalfa or chemical fallow. On the other hand, our results comply to those by Vandemark et al [ 18 ] who found that for the majority of minerals in lentil seed the highest interaction effect was the location × year (i.e., Environment) effect in two locations in Washington (US).…”
Section: Discussionsupporting
confidence: 92%
“…For seed K, contents ranged from 0.80% in E8 to 1.30% in E7 (Thessaloniki/2020) under organic farming and from 0.87% in E2 (Larissa/2019) to 1.20% in E5 (Domokos/2020) under conventional farming. On absolute terms, seed P and K contents are more or less close to or slightly different from the ranges (P: 0.29–0.41%; K: 0.81–0.92%) reported in the study by Chen et al [ 47 ] for 15 environments in Montana (US) and comparable to those (P: 0.40–0.46%; K: 0.96–1.06%) reported in the study by Vandemark et al [ 18 ] in two locations in Washington (US). Notably, seed P and K contents were higher in the second wetter year (2020) as compared to those in 2019 growing season under both farming systems indicating that ample soil moisture conditions may have favored the uptake and accumulation of these nutrients from soil and translocation to the seed.…”
Section: Discussioncontrasting
confidence: 53%
See 3 more Smart Citations